Assessment of Salivary α-amylase and Flow Rate Levels and Their Correlation with Gingivitis and Severity of Chronic Periodontitis (Part: 1) - Haider J. Talib; Maha A. Ahmed (College of Dentistry/ University of Baghdad, 2016)
Background: Periodontal diseases are bacterial infections of the gingiva, bone and attachment fibers that support the teeth and hold them in the jaw. α-amylase is an enzyme, produced mainly by parotid gland and it seems to play a role in maintaining mucosal immunity. Aims of the study: Determine the salivary levels of α-Amylase and flow rate and their correlations with clinical periodontal parameters(Plaque Index , Gingival Index , Bleeding on Probing , Probing Pocket Depth , and Clinical Attachment Level ) and the correlation between α-Amylase with flow rate of study groups that consist of ( patients had gingivitis and patients had chronic periodontitis with different severities(mild ,moderate ,severe) and control group . Materials and Methods: Salivary α-Amylase and flow rate levels with clinical periodontal parameters(Plaque Index , Gingival Index , Bleeding on Probing , Probing Pocket Depth , and Clinical Attachment Level ) were measured from 75 males , age ranged (30-45) years old, that divided into study groups(group of 45chronic periodontitis patients with different severities which sub-grouped into (Mild=15, Moderate=15 and Severe=15), group of 15 patients with gingivitis) and control group comprised 15 subjects had clinically healthy periodontium. Results: The levels of salivary α-amylase in patients had chronic periodontitis were the highest followed by patients had gingivitis .Highly significant differences were demonstrated between each pairs of chronic periodontitis subgroups hence, the highest level at severe chronic periodontitis subgroup patients. Flow rate decreased in gingivitis group and chronic periodontitis with its different severities. Highly significant strong positive correlations were found between α-amylase with clinical periodontal parameters at all groups and subgroups. Conclusions: The findings of the present study suggest that salivary α-Amylase can help to monitor the progression of the periodontal disease.